Sources of spiritual well-being in advanced cancer. Issue 2 (14th July 2011) - Lo, Christopher; Zimmermann, Camilla; Gagliese, Lucia; Li, Madeline; Rodin, Gary
Abstract : Objective: To test a conceptual model of sources of spiritual well-being in patients facing life-limiting disease. Design: Cross-sectional survey. Setting: Princess Margaret Hospital, Toronto, Canada. Participants: 747 patients with stage IV gastrointestinal, breast, genitourinary or gynaecological cancer, or stage IIIA, IIIB or IV lung cancer, recruited from 2002 to 2008. Main outcome measure: Spiritual well-being as assessed by the FACIT-Sp-12. Results: Using structural equation modelling, spiritual well-being was specified as being predicted by religiosity, self-esteem, social relatedness and the physical burden of disease. The model had a good fit, Comparative Fit Index=0.96, Non-normed Fit Index=0.94, Root Mean Square Error of Approximation=0.057. Standardised path coefficients relating each factor to spiritual well-being were as follows: religiosity 0.50, social relatedness 0.28, self-esteem 0.26 and physical burden −0.11. Conclusions: The authors confirmed our theoretical model in which spiritual well-being is positively associated with religiosity, self-esteem and social relatedness, and is negatively associated with physical suffering. Our findings support a multidimensional approach to spiritual well-being that addresses not only religious issues, but also pain and symptom control, and the potentially damaging effects of advanced disease on self-worth and close relationships. The spiritually informed clinical encounter may be one in which sufficient time and opportunity for reflection are afforded to consider illness trajectories and treatment decisions in the context of religious beliefs and personal values, self-worth, support systems and concerns about dependency.